Nutraceutical Potentials of Cissus populnea Linn Cultivated in the Southern Guinea Savanna Agroecology of Nigeria (Global Journal of Science Frontier Research, 2023)
Abstract not found
Keywords: cissus populnea; phytochemical screening; proximate; mineral; amino; acid vitamin analysis; medicinal plants